Studi terhadap BSI Kantor Cabang Arifin Ahmad Pekanbaru : Peran Perbankan Syariah dalam Membantu Perusahaan Kecil dan Menengah - Irwandi (Jurnal At-Tamwil: Kajian Ekonomi Syariah, 2023)
The purpose of this study is to find out how Islamic banking helps small and medium businesses at the BSI Arifin Ahmad Pekanbaru branch office. This research is classified as field research, and the approach used is a qualitative descriptive approach. This study uses a purposive sample selection method, which means that the sample selection is based on the research topic. The results of the study show that the BSI Arifin Ahmad Pekanbaru branch office has carried out empowerment through financing, consulting on business development, business guidance through seminars, and comparative studies with similar businesses that have developed and reduced poverty. Of the 10 customers surveyed, 7 said that their business had increased since BSI implemented the empowerment role, while 3 others said that their business had not increased.